Penerapan Algoritma Pencarian Binary Search dan QuickSort pada Aplikasi Kamus Bahasa Palembang Berbasis Web - Andri Andri (Jurnal Informatika: Jurnal Pengembangan IT, 2019)
Dictionaries can be used as a means to find meaning and meaning in a word. Palembang language is one of the regional languages in the province of South Sumatra. In their daily lives besides using Indonesian, the Palembang people also use the Palembang language as a means of communication with each other. This study aims to create a web-based Palembang language dictionary application so that it can be accessed using internet media. This dictionary application was created to help people who are not native to the city who live in the city of Palembang. This dictionary application provides a simple user interface that makes it easy for users to use it. In the development of this dictionary application is made using the RAD method. The search algorithm used in word search in a database is using the binary search method. The binary search method has the advantage of linear search. In practice binary search searches by first dividing into two data in a database that has been sorted first. This application can do an effective word search and the information displayed in this application in addition to the meaning and meaning of the word also provides an example of how to use the searched word in Palembang sentences.